Analisis Karakter Peduli Lingkungan Siswa Sekolah Dasar Negeri Adiwiyata II Bangoan Tulungagung - Rohmatus Syafi'ah; Kevin Sandy (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
The caring character for the environment is an attitude and an action to prevent the environmental damage. The purpose of this study is to describe Students’ Caring Character for the environment at Bangoan II Elementary Adiwiyata School, Tulungagung. The type of approach in this research was qualitative with descriptive methods. The research subjects Were 2A, 3A, 4A, and 5A grade students of Bangoan II Elementary Adiwiyata School which each group is consisted of 5 students. The reaserch data was collected by using questionnaire instruments and interview sheets. The results showed that students of SD Negeri II Bangoan have a high character of environmental care. The research result has shown that the students highly have environmental caring character which is supported by using a questionnaire and interview that is included four indicators of environmental care including: energy saving, waste management, water utilization, and caring for the surrounding environment. Based on this result, authors concluded that  the 3A Grade Students' caring character are higher than the 2A, 4A, and 5A grade student which are showed that 3A Grade Students' caring character is in very high category, while the 2A, 4A, and 5A is in very high category. In conclude, Students’ Caring Character for the environment at Bangoan II Elementary Adiwiyata School Tulungagung is high